Rice waste biochars produced at different pyrolysis temperatures for arsenic and cadmium abatement and detoxification in sediment. (July 2020) - Zhang, Wei; Tan, Xiaofei; Gu, Yanling; Liu, Shaobo; Liu, Yunguo; Hu, Xinjiang; Li, Jiang; Zhou, Yahui; Liu, Sijia; He, Yuan
Abstract: The effectiveness of rice waste biochars on heavy metal and metalloid abatement and detoxification was investigated using comprehensive studies based on As and Cd immobilization, bioaccumulation in tubifex, and microbial community changes in contaminated sediment. The remediation effects of biochars produced at different pyrolytic temperatures (400–700 °C) were evaluated. Bioaccumulation of heavy metal and metalloid in the tubifex tissue and change of indigenous microbial community under treatment of different biochars were assessed. Biochars produced at 700 °C exhibited greater effect on decreasing the concentrations of As and Cd in aqueous phase, and TCLP extractable and bioavailable metal(loid) in solid phase of sediment. The concentration of As and Cd in water phase decreased by 26%–89% and 22%–71% under the treatment of straw biochar, and decreased by 13%–92% and 5%–64% under the treatment of rice husk biochar, respectively. As and Cd contents in the tubifex tissue were positively correlated with their concentrations in aqueous phase. High-temperature biochars significantly reduced metal(loid) bioaccumulation in tubifex. The richness and biodiversity of microbial community were both greater in all biochars remediated sediment compared to non-treated sediment. These results indicated that rice waste biochars could effectively inhibit the bio-availability and toxicity of heavy metal and metalloid in sediment, and the higher-temperature biochar exhibited better performance. Graphical abstract: Image 1 Highlights: Rice waste biochars were effective for metals abatement and detoxification in sediment. High-temperature biochars exhibited greater effect on heavy metal immobilization. High-temperature biochars reduced heavy metal bioaccumulation in Tubifex tubifex. Biochars could increase the microbial richness and biodiversity of sediment.